Implementation and Teachers’ and Students’ Perceptions Toward English Program at Darunnajat Islamic Modern Boarding School - Izzan Kariman; M. Happy Nur Tsani; Yasinta Wulandari (Surakarta English and Literature Journal, 2024)
ABSTRACT This research aimed to explore the implementation of the English program and teachers’ and students’ perceptions toward the English program at Darunnajat Islamic Modern Boarding School. The subjects of this research were two English teachers and forty students of Darunnajat Islamic Modern Boarding School. Mixed-method research was applied to describe the implementation of the English program and teachers’ and students’ perceptions toward the English program at Darunnajat Islamic Modern Boarding School. The researcher used observation, interviews, questionnaires, and documentation to collect data from the subjects. The result shows that the implementation of the English program in Darunnajat Islamic Modern Boarding School includes English public speaking, English courses, and English conversation. Teachers and students gave positive and negative perceptions of the English program at Darunnajat Islamic Modern Boarding School. Based on teachers’ perceptions, the English program has very important benefits, and functions and makes students more confident, even though they also think that the program is burdening for students who dislike it. Based on students’ perceptions, the English program can help students be more disciplined and communicative. However, they think that the program cannot give enough motivation to practice speaking and improve their vocabulary mastery